Design of Anode-Electrolyte Interface Towards Better Solid-State Lithium Batteries - Cao, Chencheng (Curtin University, 2024)
Since their commercial debut in 1991, lithium-ion batteries (LIBs) have become ubiquitous despite challenges like combustibility and limited energy density. Scientists focus on utilizing lithium metal in the anode to boost performance. Transitioning from liquid to solid electrolytes, particularly garnet-type SSEs, shows promise in reducing dendrite formation and enhancing conductivity. The aim is to engineer robust solid-state lithium batteries (SSBs) with durable electrode-electrolyte interfaces.